Graziaphylus, a new genus and two new species of Eremophila-feeding (Scrophulariceae) Phylinae (Insecta: Heteroptera: Miridae) from Australia - Schuh, Randall T.; Salas, Ruth (Zootaxa, 2021)
The new genus Graziaphylus is described to include two new species, Graziaphylus joceliae and G. nigripes. This new taxon is part of a large suite of Heteroptera from Australia known to feed on species of Eremophila (Scrophulariaceae), including other members of the Miridae as well as the Tingidae. The appearance of Graziaphylus spp. is similar to that of Xiphoidellus Weirauch and Schuh from Australia, and to Chlamydatus Fieber from the Northern Hemisphere (among other genera), but with scalelike setae, and elongate pulvilli adnate over most of the claw length, and the distinctive structure of the male genitalia.